THE INFLUENCE OF ENTREPRENEURIAL ORIENTATION ON DIGITAL MARKETING AND SUSTAINABLE COMPETITIVE ADVANTAGE - Karina Utami Anastuti; Khoiriyah Trianti (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2024)
This research aims to determine the influence of entrepreneurial orientation on digital marketing and sustainable competitive advantage. The sample used in this research was 314 restaurants in Malang City with a stratified random sampling technique and the method used was proportionate random sampling. This research uses path analysis with smartPLS to find out how much influence entrepreneurial orientation with six indicators (innovativeness, risk-attitude, proactiveness, autonomy, aggressiveness, competitiveness) has on digital marketing as measured by 4C (co-creation, currency, communal activation, conversation) and sustainable competitive advantage as measured by indicators (scarce corporate value, imitability, durability, transferability). In this research, entrepreneurial orientation can encourage an increase in sustainable competitive advantage in a number of restaurants in Malang City. Entrepreneurial orientation can encourage increased digital marketing for restaurant businesses in Malang City. Entrepreneurial orientation is a creative and innovative ability that is used as the basis and resource for seeking opportunities for success. Furthermore, entrepreneurship not only requires knowledge but also skills. Entrepreneurial competence is needed in implementing marketing strategies in order to obtain a solid competitive advantage through the value of responsiveness to customer needsKeywords: Entrepreneurship Orientation, Digital Marketing, Sustainable Competitive Advantage